Augmented Liver Uptake of the Membrane Voltage Sensor Tetraphenylphosphonium Distinguishes Early Fibrosis in a Mouse Model - Pandita, Himanshi; Mezey, Esteban; Ganapathy-Kanniappan, Shanmugasundaram (Frontiers in Physiology, 2021)
Mitochondrial (mito-) oxidative phosphorylation (OxPhos) is a critical determinant of cellular membrane potential/voltage. Dysregulation of OxPhos is a biochemical signature of advanced liver fibrosis. However, less is known about the net voltage of the liver in fibrosis. In this study, using the radiolabeled [3H] voltage sensor, tetraphenylphosphonium (TPP), which depends on membrane potential for cellular uptake/accumulation, we determined the net voltage of the liver in a mouse model of carbon tetrachloride (CCl4)-induced hepatic fibrosis. We demonstrated that the liver uptake of 3H-TPP significantly increased at 4 weeks of CCl4-administration (6.07 ± 0.69% ID/g, p < 0.05) compared with 6 weeks (4.85 ± 1.47% ID/g) and the control (3.50 ± 0.22% ID/g). Analysis of the fibrosis, collagen synthesis, and deposition showed that the increased 3H-TPP uptake at 4 weeks corresponds to early fibrosis (F1), according to the METAVIR scoring system. Biodistribution data revealed that the 3H-TPP accumulation is significant in the fibrogenic liver but not in other tissues. Mechanistically, the augmentation of the liver uptake of 3H-TPP in early fibrosis concurred with the upregulation of mito-electron transport chain enzymes, a concomitant increase in mito-oxygen consumption, and the activation of the AMPK-signaling pathway. Collectively, our results indicate that mito-metabolic response to hepatic insult may underlie the net increase in the voltage of the liver in early fibrosis.